Інформаційна система надання рекомендацій туристичних маршрутів - Петрів, Володимир Ігорович; Petriv, Volodymyr Ihorovych (Національний університет "Львівська політехніка", 2024)
Актуальність теми магістерської роботи "Інформаційна система надання рекомендацій туристичних маршрутів" зумовлена низкою вагомих чинників: Зростання попиту на індивідуальні туристичні послуги. У сучасних умовах розвитку індустрії туризму користувачі все більше очікують персоналізованого підходу. Система, яка формує маршрути відповідно до інтересів, побажань і обмежень мандрівника, значно спрощує процес вибору і планування поїздки. Технологічний прогрес і доступність великих даних. Широке впровадження штучного інтелекту та методів машинного навчання дозволяє аналізувати великі масиви інформації, що відкриває нові можливості для створення рекомендаційних систем, які враховують географічні, культурні, соціальні й інші чинники. Потреба у зручності та адаптації сервісів. Багатьом користувачам складно самостійно обрати маршрути подорожі. Автоматизована система рекомендацій значно полегшує цей процес і дозволяє адаптувати подорож до індивідуальних потреб. Конкурентні переваги для туристичних компаній. Інноваційні сервіси підвищують привабливість компанії в очах клієнтів. Можливість надання персоналізованих маршрутів сприяє зміцненню лояльності та розширенню клієнтської бази. Покращення досвіду користувача. Система, що враховує безліч параметрів – від бюджету до сезонності – допоможе створити оптимальний маршрут і зменшити стрес під час планування. Метою магістерської роботи є створення інформаційної системи, яка автоматично надає персоналізовані рекомендації туристичних маршрутів з урахуванням уподобань, бюджету, тривалості поїздки та інших параметрів. Основні завдання дослідження: Дослідити потреби користувачів і визначити функціональні вимоги до системи. Розробити ефективні алгоритми формування маршрутів на основі введених даних. Створити інтуїтивний інтерфейс користувача. Забезпечити інтеграцію з зовнішніми джерелами даних і туристичними базами. Провести тестування системи, оцінити її ефективність та оптимізувати роботу. Об’єкт дослідження – процес формування рекомендацій туристичних маршрутів. Предмет дослідження – методи і засоби створення таких рекомендацій. Наукова новизна полягає у: Розробці нових алгоритмів, що враховують не лише популярність напрямків, але й унікальні характеристики користувача – його інтереси, стан здоров’я, рівень активності тощо. Інтеграції різноманітних джерел інформації – соціальних мереж, карт, оглядів, сервісів у реальному часі. Застосуванні технологій Big Data і машинного навчання для покращення персоналізації. Орієнтації системи на різні категорії користувачів, включно з людьми з особливими потребами. Використанні чат-ботів та голосових помічників для зручної взаємодії. Залученні геопросторових технологій для формування маршрутів на інтерактивних картах. Практична цінність роботи: Туристи зможуть швидко та зручно обирати найкращі варіанти подорожей відповідно до власних умов. Туристичні компанії отримають потужний інструмент для покращення сервісу і залучення клієнтів. Система сприятиме розвантаженню популярних маршрутів і розвитку нових туристичних напрямків. Завдяки доступності через голосових помічників і інтерактивні мапи – система буде корисною для широкого кола користувачів, включно з малодосвідченими або маломобільними людьми. Пропонуючи нові локації, система може підтримувати локальний бізнес і сприяти сталому розвитку регіонів. Дані, що збиратимуться системою, можуть бути використані для подальшого вдосконалення сервісів та розробки нових продуктів. Таким чином, результати роботи мають як теоретичне, так і практичне значення для фахівців туристичної галузі та кінцевих користувачів, забезпечуючи персоналізований і комфортний досвід подорожей.

The relevance of the master's thesis titled "Information System for Recommending Tourist Routes" is determined by several significant factors: Growing demand for personalized travel services. In the modern tourism industry, users increasingly expect a personalized approach. A system that generates routes based on the traveler’s preferences, interests, and limitations greatly simplifies the travel planning process. Technological advancements and big data accessibility. The widespread use of artificial intelligence and machine learning enables the analysis of large datasets, opening new possibilities for developing recommendation systems that take into account geographic, cultural, social, and other relevant factors. Need for user-friendly and adaptive services. Many travelers face difficulties when planning their trips. An automated recommendation system can greatly facilitate this process and tailor the travel plan to individual needs. Competitive advantages for travel companies. Innovative services enhance a company’s appeal to clients. Offering personalized routes contributes to customer loyalty and expands the client base. Enhancing the user experience. A system that considers multiple factors–such as budget, timing, and seasonality–can help generate an optimal route while reducing the stress involved in planning. The goal of this thesis is to develop an information system that automatically provides personalized tourist route recommendations based on the user’s preferences, budget, duration of the trip, and other parameters. The main objectives of the research include: Analyzing user needs and identifying functional requirements for the system. Developing effective algorithms for generating routes based on user-provided data. Creating an intuitive and user-friendly interface. Ensuring integration with external databases and tourist information sources. Testing the system’s performance, evaluating its efficiency, and optimizing its operation. Object of study – the process of generating tourist route recommendations. Subject of study – methods and tools for providing such recommendations. Scientific novelty of the work includes: Designing new algorithms that consider not only general factors like popularity or budget, but also individual characteristics such as interests, travel history, physical condition, and even mood. Integrating various information sources – such as social media, maps, reviews, and real-time data – into a unified system. Applying big data analysis and machine learning techniques to improve personalization based on user history, ratings, preferences, and real-world data. Adapting the system for different user groups, including children, elderly travelers, individuals with special needs, adventure seekers, and others – taking into account physiological characteristics, health, and experience. Incorporating chatbots, virtual assistants, or voice interfaces to enhance usability and enable communication in natural language. Utilizing geospatial technologies for route creation on interactive maps that account for distance, travel time, transportation availability, road conditions, and tourist attractions along the way. Practical value of the work: The developed recommendation system will help users quickly find optimal routes tailored to their interests, conditions, and needs (e.g., time, budget, physical fitness). This simplifies trip planning and saves time. Travel companies can offer an innovative and user-friendly service, gaining a competitive edge and increasing customer loyalty. The system promotes visits to less-known destinations, easing the burden on overcrowded tourist sites and contributing to sustainable tourism. Thanks to interactive maps, voice assistants, and chatbots, the system becomes accessible to a broader audience, including individuals with limited experience or mobility. By suggesting routes that include local spots, the system can support small businesses like hotels, restaurants, and shops, promoting regional development. The system collects user feedback and preferences, which can be analyzed to enhance the service and develop new products. It can be integrated with booking platforms for tickets, hotels, and transport, forming a unified travel ecosystem across all stages of the journey. Thus, the results of this thesis have wide practical applications for travel companies, infrastructure development organizations, and end users – travelers seeking more personalized and convenient trip planning tools
Information System for Providing Recommendations for Tourist Routes
Keywords: 3.126.00.00